Pengaruh Orientasi Kepemimpinan Pasar dan Strategi Inovasi terhadap Kinerja UKM (Studi pada UKM Kerajinan Bubut Kayu Kota Blitar) - Perwiranegara, Abdul Haris (Jurnal Aplikasi Manajemen, 2015)
This study aimed to analyze the influence among variables in order to answer the question of how the market leadership orientation and the innovation strategy on small and medium enterprises (SME) will improve its performance. This study focuses on Blitar wood lathe.This research is explanation (explanatory research), in which it explains the causal relationship between research variables through hypothesis testing. Population of research is the wood lathe SME that operating in the Blitar city. Sample is taken by simple random sampling technique with a sample size of 110 units. The results concluded that the orientation of the market leadership directly affects SMEs on innovation process, product innovation and organizational innovation. Process innovation and product innovation has a direct influence on the performance of SME. Only organization innovation does not have a significant effect on the SME performance. Then, the market leadership orientation has no direct effect on the SME performance but it's have indirectly affect on the performance of the organization through process innovation and product innovation.